MEMPREDIKSI MASA STUDI MAHASISWA MENGGUNAKAN METODE JACCARD COEFFICIENT (Studi Kasus: Mahasiswa Program Studi Teknik Informatika Jurusan Teknik Elektro Fakultas Teknik Universitas Tanjungpura) - Hafidh, Khairul (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2015)
The rapid growth of education and competitive create conditions for each college to continue to improve the quality especially with college accreditation assessment of BAN-PT. Informatics which is one of the undergraduate program (S1) at the University of Tanjungpura Pontianak in regular class on 2010 batch was graduating only 3 of 35 students in 8 semesters. This shows that there is still a lot of Informatics students who took over the study period of 8 semesters of the scheduled 8 semesters. One way to achieve the highest quality quality of higher education system is to collect data as attributes of the main learning experiences that affect student achievement. Analysis prediction graduate student more than 8 semesters is to conduct case-based reasoning is to find the degree of similarity between the cases base with new cases (cases to be predicted). The main source of knowledge is a case-based reasoning system based on the cases that have been or are already stored in the cases base. Cases are obtained to support this research was obtained from the results of interviews with graduates from 2003 to 2010 generation. Case-based reasoning process through four stages: Retrieve (penulusuran case), Reuse (using the same solution in the cases base), Revise (revise the proposed solution), and Retain (storage case). Case similarity calculation was conducted using the Jaccard Coefficient. If the similarity value = 1 then the new cases are not stored in the cases base, but if the similarity value <1 then a new case can be saved in the cases base. Testing the system with the Jaccard Coefficient to the 31 new cases have a value of 80.65% accuracy.